Preparation of cobalt-based oxide and its application in catalytic absorption of co2 in amine solution

CN122999200APending Publication Date: 2026-10-30XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611469010.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,纳米流体颗粒易团聚、沉积,对MDEA溶液中CO2吸收活性的改善程度相对有限,主要原因在于其作用机制更多依赖物理增强

Benefits of technology

[0025](1)催化剂制备过程工艺简单,原料便宜易得。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999200A_ABST
    Figure CN122999200A_ABST
Patent Text Reader

Abstract

The application discloses a kind of preparation of cobalt-based oxide and its application in catalytic amine solution absorption CO2 process, method includes the following steps: (1) soluble metal salt is dissolved in water, precipitant and surfactant are added to obtain mixed solution;(2) after the mixed solution is ultrasonically in ultrasonic cleaner for a certain time, it is transferred to polytetrafluoroethylene lining, and is put into reaction kettle hydrothermal;(3) after hydrothermal, the precipitate obtained is washed with water, washed with ethanol, dried, ground, calcined, to obtain the cobalt-based oxide catalyst.The catalyst of the application can be used for catalyzing the absorption of CO2 in tertiary amine solution, the catalyst preparation process is simple, low in cost, green and clean.Because of the rich oxygen vacancy, its catalytic tertiary amine solution absorption CO2 performance is superior, and the cycle stability is high, has good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon dioxide capture technology, specifically relating to the preparation of cobalt-based metal oxide catalysts such as CoOOH, CoO, Co2O3, and Co3O4 and their application in the catalytic absorption of CO2 from amine solutions. Background Technology

[0002] Among numerous CO2 capture technologies, chemical absorption has become the mainstream technology for large-scale industrial application due to its significant advantages such as high capture efficiency and mature technology. Organic amine solvents can be mainly divided into three categories: primary amines (such as monoethanolamine MEA), secondary amines (such as diethanolamine DEA), and tertiary amines (such as N-methyldiethanolamine MDEA). Although primary and secondary amines have relatively fast CO2 absorption rates, they readily react with CO2 to form stable carbamates, resulting in high energy consumption for solvent regeneration. Furthermore, the regeneration energy consumption of primary amines can account for up to 60% of the total capture cost, significantly increasing CO2 capture costs and hindering its large-scale industrial application.

[0003] In contrast, tertiary amine absorbents such as N-methyldiethanolamine (MDEA) exhibit unique advantages. Tertiary amine molecules lack hydrogen atoms directly bonded to nitrogen atoms, so they cannot react directly with CO2. Instead, they promote the hydration of CO2 through a base-catalyzed mechanism, generating protonated amines (MDEAH). + ) and bicarbonate ions (HCO3) - But HCO3 - Tertiary amine solvents have low stability and are prone to decomposition, releasing CO2. Therefore, they consume less energy during desorption and possess better resistance to degradation and corrosion. However, the slow rate of CO2 absorption by tertiary amine solvents remains a major challenge for current industrial development.

[0004] To address this issue, many researchers have enhanced CO2 absorption rates by adding nanoparticles. For example, Baghery et al. added amine-functionalized carbon nanotubes to the solvent to improve mass transfer. The optimal concentration of NH2-MWCNT nanofluids was 0.5 wt%, which increased the CO2 absorption rate of a 10% MDEA solution by 21% under the highest pressure (200 psi) and 40 °C (Journal of Molecular Liquids, 2019, 293: 111431). Zhang et al. found that synthesizing porous carbon spheres Co@C and Fe@C could increase the CO2 absorption rate of a 30 wt% MDEA solution by 15% and 16% respectively at 24 °C (Separation and Purification Technology, 2025, 362: 131674). However, nanofluid particles are prone to aggregation and deposition, resulting in relatively limited improvement on CO2 absorption activity in MDEA solutions, mainly because their mechanism of action relies more on physical enhancement.

[0005] Solid catalysts can provide abundant surface active sites, lower reaction energy barriers, and significantly accelerate CO2 hydration and proton transfer rates in tertiary amine systems, thereby significantly improving absorption kinetics. Among them, Zhang et al. used manganese-based oxides to catalyze and promote CO2 absorption by MDEA. The synergistic effect of its high concentration of basic sites and unsaturated Mn sites effectively promoted the absorption of CO2 by MDEA solution. The absorption rate and absorption capacity were significantly increased by 360% and 132%, respectively (Chemical Engineering Journal, 2023, 465: 142878). Elhambakhsh et al. increased the CO2 absorption capacity of 5 wt% MDEA solution at 35°C by 8.7% by adding a CeO2 / SiO2 / TiO2 composite material (Chemical Papers, 2022, 76(8): 4817-4834). Therefore, developing low-cost, highly active, and stable catalysts to enhance the CO2 absorption performance of tertiary amine solvents and constructing a CO2 capture system with high absorption rate and low regeneration energy consumption has significant theoretical research value and industrial application prospects. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a cobalt-based oxide solid base catalyst and its application in catalytic CO2 absorption. The preparation method is simple, and the prepared catalyst enhances the rapid absorption of CO2 by tertiary amine solution, thereby increasing the CO2 absorption rate and reducing the cost of CO2 capture.

[0007] The present invention provides a method for preparing a cobalt-based oxide (Co3O4) catalyst for catalytically enhanced CO2 absorption from tertiary amine solutions, comprising the following steps:

[0008] (1) Weigh a certain amount of cobalt salt, precipitant and surfactant, mix them and add distilled water to obtain a mixed solution;

[0009] (2) Sonicate the mixed solution for 20-40 min;

[0010] (3) The mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment, and the precipitate was obtained after the reaction was completed;

[0011] (4) The precipitate was washed with water, washed with ethanol, dried and ground to obtain the precursor;

[0012] (5) The precursor is placed in a crucible and calcined to obtain the Co3O4 catalyst.

[0013] Preferably, in step (1), the molar ratio of cobalt salt and precipitant is 1:1, 1:2, or 2:1 for Co:N.

[0014] Preferably, in step (1), the cobalt salt is at least one of cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, and cobalt carbonate.

[0015] Preferably, in step (1), the precipitant is at least one of urea, hexamethylenetetramine, sodium hydroxide, potassium hydroxide, and ammonium carbonate.

[0016] Preferably, in step (1), the surfactant is at least one of polyvinylpyrrolidone (PVP), hexadecyltrimethylammonium bromide (CTAB), and polyethylene glycol (PEG).

[0017] Preferably, in step (3), the hydrothermal temperature is 80-110 ℃ and the time is 10-16 h;

[0018] Preferably, in step (4), the drying temperature is 60-90 ℃ and the time is 2-8 h;

[0019] Preferably, in step (5), the calcination temperature is 200-400 ℃, the time is 3-5 h, and the heating rate is 5 ℃ / h;

[0020] This invention also provides the application of cobalt-based oxide solid base catalysts in the catalytic absorption process of tertiary amine solvents.

[0021] Preferably, the tertiary amine solvent includes N-methyldiethanolamine (MDEA), dimethylaminoethanol (DMEA), 4-diethyl-2-butanol (DEAB), 1-diethylamino-2-propanol (1DEA2P), 1-(2-hydroxyethyl)pyrrolidine (1-(2-HE)PRLD), 1-(2-hydroxyethyl)piperidine (1-(2-HE)PP), 4-ethyl-methyl-amino-2-butanol (EMAB), triethanolamine (TREA), and triethylamine. One or more of the following: (TEA), 4-diethylamino-2-butanol (DEAB), 3-dimethylamino-1-propanol (3DMA1P), 1-dimethylamino-2-propanol (1DMA2P), N-methyl-4-piperidine (MPDL), tetramethyldiethylamine (TMEDA), tetramethyldipropylamine (TMPDA), tetramethyldibutylamine (TMBDA), 4-amino-1-methylpiperidine (4-AlMPD), N,N-diethylethanolamine (DEEA).

[0022] Preferably, the amount of the cobalt-based oxide catalyst is 0.5-1.0 wt%, and the absorption stirring speed is 300-800 r / min.

[0023] Preferably, the CO2-containing gas is flue gas emitted from a coal-fired power plant, with a CO2 content of 10-20 vol% and an N2 content of 80-90 vol%.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] (1) The catalyst preparation process is simple and the raw materials are cheap and readily available.

[0026] (2) The catalyst has excellent absorption performance and its catalytic performance is superior to that of oxides such as SiO2 and TiO2.

[0027] (3) The catalyst is easy to separate, has good stability, and good recyclability. Attached Figure Description

[0028] Figure 1 Diagram of the experimental setup for CO2 absorption by tertiary amines;

[0029] Figure 2 The graph shows the CO2 absorption rate of tertiary amine solutions catalyzed by the three catalysts prepared in Examples 1, 2, 3 and Comparative Example 1.

[0030] Figure 3 The graph shows the absorption of tertiary amine solutions by the three catalysts prepared in Examples 1, 2, 3, and Comparative Example 1.

[0031] Figure 4The graph shows the relative rates of CO2 absorption by tertiary amine solutions catalyzed by the four catalysts prepared in Examples 1, 2, 3, and Comparative Example 2.

[0032] Figure 5 X-ray diffraction patterns of the three catalysts prepared in Examples 1, 2 and 3;

[0033] Figure 6 Fourier transform infrared spectra of the three catalysts prepared in Examples 1, 2 and 3;

[0034] Figure 7 Raman spectra of the three catalysts prepared in Examples 1, 2 and 3;

[0035] Figure 8 The graph shows the absorption performance of the catalyst prepared in Example 1 after 10 cycles. Detailed Implementation

[0036] The present invention will be further described in detail below with reference to specific embodiments.

[0037] Example 1

[0038] Preparation of Co3O4 metal oxide catalysts:

[0039] (1) Weigh 2.91 g of cobalt nitrate hexahydrate, 0.6 g of urea and 0.25 g of polyvinylpyrrolidone, and add 100 mL of distilled water to obtain a mixed solution;

[0040] (2) Sonicate the mixed solution for 20 min;

[0041] (3) Pour the sonicated solution into a 250 ml polytetrafluoroethylene liner and place it in a reaction vessel to react at 100 °C for 12 h;

[0042] (4) After the reaction is completed and cooled, filter the precipitate, wash it several times with water and ethanol, put it in an oven at 90 °C and dry it for 4 h to obtain a light purple precipitate.

[0043] (5) The dried precipitate was ground into powder and placed in a crucible and calcined in a muffle furnace at 300 °C for 4 h. The metal oxide Co3O4 catalyst was obtained.

[0044] The Co3O4-1 catalyst prepared in this embodiment was added to a tertiary amine solution and subjected to catalytic absorption experiments at room temperature (24 °C). The amount of Co3O4-1 catalyst added to the tertiary amine was 0.5 g. The absorption results are shown in [Figure number missing]. Figure 2 and Figure 3 .

[0045] Example 2:

[0046] The preparation of Co3O4-2 was as follows: 17.46 g of cobalt nitrate hexahydrate was dissolved in 100 ml of water to obtain solution A; 17.96 g of potassium hydroxide was dissolved in 100 ml of water to obtain solution B. Solution B was then added dropwise to solution A with stirring, resulting in a precipitate. The precipitate was filtered, washed, and dried at 100 °C for 20 h. The dried precipitate was then calcined in a muffle furnace at 300 °C for 4 h to obtain Co3O4-2.

[0047] The prepared Co3O4-2 catalyst was added to a tertiary amine solution and subjected to catalytic absorption experiments at room temperature (24 °C). The amount of Co3O4-2 catalyst added to the tertiary amine was 0.5 g. The absorption results are shown in the figure. Figure 2 and Figure 3 .

[0048] Example 3:

[0049] The preparation of Co3O4-3 was as follows: 50 ml of a 1 mol / L cobalt sulfate solution was prepared as solution C. A 5 mol / L sodium carbonate solution was slowly added dropwise to the solution to achieve a pH of 9.4-9.8. Solution C was stirred continuously for 1 h to obtain a deep purple suspension. After filtration and washing with water, the suspension was dried in an oven at 90 ℃ for 12 h to obtain a precipitate. The dried precipitate was then calcined in a muffle furnace at 300 ℃ for 4 h to obtain Co3O4-3.

[0050] The prepared Co3O4-3 catalyst was added to a tertiary amine solution and catalytic absorption experiments were conducted at room temperature (24 °C). The amount of Co3O4-3 catalyst added to the tertiary amine was 0.5 g. The absorption results are shown in the figure. Figure 2 and Figure 3 .

[0051] Figure 2 and Figure 3 The graphs show the CO2 absorption performance of the Co3O4-1, Co3O4-2, and Co3O4-3 catalysts prepared for Examples 1, 2, and 3, respectively, in a 20% concentration tertiary amine solution. The results indicate that the addition of catalysts can improve the CO2 absorption rate to varying degrees. Among them, the Co3O4-1 catalyst exhibits the best catalytic absorption effect. Compared with the blank without catalyst, the Co3O4-1 catalyst increased the CO2 absorption rate by 246% (425 s) and the CO2 absorption capacity by 97% (770 s). This is likely due to the abundant oxygen vacancies in the Co3O4-1 catalyst.

[0052] Comparative Example 1

[0053] The absorption experimental conditions and the calculation methods for CO2 absorption rate and CO2 absorption amount were the same as in Example 1, except that no catalyst was added and the result was recorded as a blank.

[0054] Comparative Example 2

[0055] In contrast, CoOOH was prepared as follows: 13.7 g of cobalt nitrate hexahydrate was completely dissolved in 250 ml of pure water, sodium hydroxide was added, and the mixture was stirred continuously to precipitate the metal ions. The precipitate was then transferred to a polytetrafluoroethylene-lined reactor and hydrothermally heated at 110°C for 12 h. The precipitate was washed with water, filtered, and dried in an oven at 60°C to obtain CoOOH.

[0056] The prepared CoOOH catalyst was added to a tertiary amine solution and subjected to catalytic absorption experiments at room temperature (24 °C). The results of the relative CO2 absorption rates are shown in the figure. Figure 4 .

[0057] Figure 5 The XRD patterns are for characterizing the three catalysts Co3O4-1, Co3O4-2, and Co3O4-3 prepared in Examples 1, 2, and 3. The diffraction peaks at 2θ = 19.3°, 31.5°, 37.2°, 38.7°, 45.2°, 59.5°, and 65.4° are attributed to the (111), (220), (311), (222), (400), (511), and (440) crystal planes of Co3O4. Co3O4-1 exhibits the sharpest peaks, highest intensity, best crystallinity, larger grain size, and higher crystal integrity. Figure 6 Fourier transform infrared (FTIR) spectra of the Co3O4-1, Co3O4-2, and Co3O4-3 catalysts prepared in Examples 1, 2, and 3, respectively. (At 558 cm⁻¹) -1 and 661cm -1 The two strong absorption bands at the point are due to the stretching vibration of Co3O4 and the bridging vibration of O-Co-O, both characteristic of the Co3O4 spinel structure. The Raman spectra of the Co3O4-1, Co3O4-2, and Co3O4-3 catalysts prepared in Examples 1, 2, and 3 are shown below. Figure 7 As shown. The crystal structure and surface defects of the Co3O4 catalyst were identified using Raman spectroscopy. The crystal structures were located at 186, 464, 509, 601, and 670 cm⁻¹. -1 The nearby peaks correspond to F respectively 2g(1) E g F 2g(2) F 2g(3) and A 1g The vibrational modes of Co3O4. Among them, those located at 186, 509, and 601 cm⁻¹. -1 The peak value is attributed to Co in the tetrahedron. 2+ -O 2- Raman vibrations, and 670cm -1 The nearby peak is attributed to Co in the octahedron. 3+ -O 2-The characteristic vibration of A. 1g Under the diffraction peaks, Co3O4-1 shows the most significant peak shift compared to Co3O4-2 and Co3O4-3, indicating that the Co-O bond in Co3O4-1 is weaker. Co3O4-1 has the largest peak width, representing a larger local lattice distortion and a higher concentration of oxygen vacancy defects. Figure 8 This is a graph showing the CO2 absorption performance of the Co3O4-1 catalyst in Example 1 after 10 cycles. The CO2 absorption rate in the initial cycle was set at 100%. Subsequent cycle experiments will use the initial cycle as a reference point to evaluate the catalytic activity ratio. Clearly, after 10 runs, the CO2 absorption capacity remains good. Therefore, the results demonstrate that the Co3O4-1 catalyst exhibits excellent stability.

[0058] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the scope of the technology disclosed in the present invention, and within the spirit and principles of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A cobalt-based oxide (Co3O4) catalyst, characterized in that, The preparation method includes the following steps: (1) Weigh a certain amount of cobalt salt, precipitant and surfactant, mix them and add distilled water to obtain a mixed solution; (2) Sonicate the mixed solution for 20-40 min; (3) The mixed solution was transferred to a polytetrafluoroethylene liner for hydrothermal treatment, and the precipitate was obtained after the reaction was completed; (4) The precipitate was washed with water, washed with ethanol, dried and ground to obtain the precursor; (5) The precursor is placed in a crucible and calcined to obtain the cobalt-based oxide catalyst.

2. As described in claim 1, characterized in that, The molar ratio of cobalt salt to precipitant is 1:1, 1:2, or 2:1 for Co:N; the cobalt salt is at least one of cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, and cobalt carbonate; the precipitant is at least one of urea, hexamethylenetetramine, sodium hydroxide, potassium hydroxide, and ammonium carbonate; and the surfactant is at least one of polyvinylpyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB), and polyethylene glycol (PEG).

3. As described in claim 1, characterized in that, In step (3), the hydrothermal temperature is 80-110 ℃ and the time is 10-16h.

4. As described in claim 1, characterized in that, In step (4), the drying temperature is 60-90 ℃ and the time is 2-8h.

5. As described in claim 1, characterized in that, In step (5), the calcination temperature is 200-400 ℃, the time is 3-5 h, and the heating rate is 5 ℃ / h.

6. The cobalt-based oxide catalyst prepared by the preparation method according to any one of claims 1 to 8.

7. The application of the cobalt-based oxide catalyst as described in claim 7 in the catalytic absorption of CO2 from a tertiary amine solution.

8. The application according to claim 10, characterized in that: The tertiary amine solvents include N-methyldiethanolamine (MDEA), dimethylaminoethanol (DMEA), 4-diethyl-2-butanol (DEAB), 1-diethylamino-2-propanol (1DEA2P), 1-(2-hydroxyethyl)pyrrolidine (1-(2-HE)PRLD), 1-(2-hydroxyethyl)piperidine (1-(2-HE)PP), 4-ethyl-methyl-amino-2-butanol (EMAB), triethanolamine (TREA), and triethylamine (T One or more of the following: EA), 4-diethylamino-2-butanol (DEAB), 3-dimethylamino-1-propanol (3DMA1P), 1-dimethylamino-2-propanol (1DMA2P), N-methyl-4-piperidine (MPDL), tetramethyldiethylamine (TMEDA), tetramethyldipropylamine (TMPDA), tetramethyldibutylamine (TMBDA), 4-amino-1-methylpiperidine (4-AlMPD), N,N-diethylethanolamine (DEEA).

9. The application according to claim 10, characterized in that: The amount of cobalt-based oxide catalyst used is 0.5-1.0 wt%, and the absorption stirring speed is 300-800 r / min.

10. The application according to claim 10, characterized in that: The gas containing CO2 is the flue gas emitted by coal-fired power plants, with a CO2 content of 10-20 vol% and an N2 content of 80-90 vol%.